Surface functionalized fluorescent PS nanobead based dual-distinct solid state sensor for detection of volatile organic compounds - Makkad, Sarabjot Kaur (Analytical Chemistry, 2018)
Solid state emitting, distinctly dual vapor sensors with high quantum yield was developed using polystyrene incorporating two fluorophores following a miniemulsion polymerization method. Selective functionalization with carboxy and amine functionality was used to decorate the resulting polystyrene nanobeads having both perylenebisimide (PBI) and oligo (p-phenylenevinylene) (OPV) fluorophores. These nanobeads with a size of 70–180 nm showed near white emission under UV light. On contact with vapors of specific electron deficient nitroaromatics OPV emission got selectively quenched to show yellow emission from the nanobeads under UV radiation. Exposure to amine vapor quashed PBI emission selectively resulting in blue emission under UV lamp. Such a vast range of color alteration from white to either blue or yellow from the same sensor makes it a true dual analyte sensor with two distinct outputs. Control of surface functionality (−COOH, −NH2, and neutral) on the nanobeads played a pivotal role in boosting the sensing efficiency; introduction of functionality on the surface facilitated analyte-sensor interaction through hydrogen bonding, prompting their fast responsiveness. Real time, potential device based application was demonstrated with free-standing films which was capable of efficient detection with fast analyte exchange from dilute solutions. Recyclability of the film sensor was demonstrated with 8 cycles of reuse.